Exposure to workplace bullying: the incremental effect of gelotophobia beyond the big five - Sulejmanov, Filip; Petr, Kryštof; Gambová, Jana; Platt, Tracey; Seitl, Martin (Frontiers in Psychology, 2024)
The role of Big Five personality traits in exposure to workplace bullying has been a focus of numerous studies. Yet less is known about the incremental validity of narrower personality constructs. The aim of the present study was to investigate the incremental effect of gelotophobia (the fear of being laughed at) in predicting exposure to workplace bullying beyond the Big Five personality domains. The sample comprised 328 employees (77% females) from different regions of the Czech Republic. Correlational analysis showed that negative emotionality and gelotophobia were related to workplace bullying in theoretically expected ways. Results from a multiple regression indicated that gelotophobia had an incremental effect in predicting exposure to workplace bullying over and above the personality domains. Overall, this study provides new insights and extends previous investigations concerning the role of gelotophobia in workplace bullying. We also discuss the limitations of our study and provide suggestions for future research.